Artificial Apis mellifera feed supplementation (Research, Society and Development, 2021)
The aim of the present study was to observe bee hive development through artificial feed supplementation and carry out drone, worker, pollen and larvae alveoli counts. The experimental treatments consisted in 1) sugar syrup: 60% sugar (crystal) + 40% water; 2) sugar and honey syrup: 60% sugar (crystal) + 40% water, plus 100 g of honey; 3) protein syrup: 60% sugar and 40% water plus 20 g of soy flour; 4) inverted syrup: five kilos of crystal sugar + 1.7 liters of water; 5) pasty food: three tablespoons of soy flour and seven tablespoons of wheat bran, adding about fifteen tablespoons of honey. The treatments were distributed in a Latin square design (5x5) using five hives and five repetitions generated over time. Each hive received one of the treatments during 21 days period, followed by a treatment-free 15-day period. Two frames from each nest were selected to carry out the counting of the alveoli, using photographs overlaid on a mapping frame consisting of 4 cm2 areas. The treatments did not influence drone and worker alveoli production. The protein syrup treatment increased the number of larvae alveoli and the sugar and honey syrup treatment was significant for the production of pollen cells.